Networks of bZIP protein-protein interactions diversified over a billion years of evolution - Reinke, Aaron W. (2013)
Differences in biomolecular sequence and function underlie dramatic ranges of appearance and behavior among species. We studied the basic region-leucine zipper (bZIP) transcription factors and quantified bZIP dimerization networks for 5 metazoan and 2 single-cell species, measuring interactions in vitro for 2,891 protein pairs. Metazoans have a higher proportion of heteromeric bZIP interactions and more network complexity than the single-cell species. The metazoan bZIP interactomes have broadly similar structures, but there has been extensive rewiring of connections compared to the last common ancestor, and each species network is highly distinct. Many metazoan bZIP orthologs and paralogs have strikingly different interaction specificities, and some differences arise from minor sequence changes. Our data show that a shifting landscape of biochemical functions related to signaling and gene expression contributes to species diversity.